Effect of Credit Risk Management on The Growth of Umurenge Saccos In Rwanda - Eliab Byamukama Mpora; David Ngatia; Ngirababo Rwusira Dan; Frank Hagumimana (International Journal of Islamic Business and Management Review, 2025)
The study established the effect of credit risk management on the growth of Umurenge SACCOS in Kigali City and the Eastern province sectors in Rwanda. Credit Risk Management was operationalized as credit risk analysis, monitoring, and risk mitigation, while growth was operationalized as Member growth, member satisfaction, and Operational efficiency. This study adopted a quantitative approach, and quantitative data were collected using Self-administration. A sample size of 84 participants was obtained using the Krejcie and Morgan 1970 table for sample determination. The findings indicate that the majority of the respondents were male, aged 31–40 years, accounting for 60.7%, and Female, 39.3%. The majority of employees are bachelor's degree holders, accounting for 54.8%, and the Secondary school level is 40.5%. The results indicate that the independent variable has a positive high correlation to the dependent variable (equal to .985** and the p-value is .000, which is less than 0.01). The limitations include bias from the respondents and the study being conducted in only Umurenge SACCO’S in Rwanda in a few Sectors this, generalizes results difficult. Managers should establish strategies and prioritize risk management practices by implementing policies in place. The findings contribute to the literature on credit risk management in terms of the Central Bank of Kigali. The study also recommends that policymakers in the financial sectors develop guidelines on how SACCOs can go about managing credit risk as credit risk management to be able to enhance the growth of wealth in SACCOs. Previous similar research only studied how credit risk management affects loan performance and the growth of SACCOs in general and particularly in other countries. The ones carried out in Rwanda did not look at Umurenge SACCO’s growth